Escola e matemática escolar: mecanismos de regulação sobre sujeitos escolares de uma localidade rural de colonização alemã no Rio Grande do Sul - Wanderer, Fernanda (Universidade do Vale do Rio do Sinos, 2007)
This thesis is the result of a research carried out with the aim to analyze the discourses on school and school mathematics of a group of German-descendant, Evangelic-Lutheran settlers who attended a rural school in Estrela-RS, at the time of the Nationalization Campaign – one of the actions taken during the Estado Novo (1937-1945), by Getúlio Vargas in Brazil. The theoretical grounds of the investigation are the post-structuralist theorizations, related to Michel Foucault’s thinking as well as to the field of Ethnomathematics, in a perspective constructed with the support of formulations of Ludwig Wittgenstein in his work Philosophical Investigations. The research material consisted of narratives produced by three women and four men who studied at the school during that period; mathematics textbooks and exercise books for copy and dictation used at the institution, and the text entitled “Schools of the past” , written by one of the participants of the research. The analytical exercise performed with the us
Keywords: colono teuto-brasileiro; ensino; história; imigração alemã; matemática; nacionalização; etnomatemática; ethnomathematics; nationalization campaign; post-structuralist theorizations; school mathematics; Ciências Humanas